2021
DOI: 10.2144/fsoa-2021-0029
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in Previously Thyroidectomized Patients: Which Thyroid Disorders are a Risk factor?

Abstract: The aim of this study was to evaluate whether there are thyroid diseases in which breast cancer will appear later as well as the role of autoimmunity. This was a retrospective observational study. A total of 410 females (thyroid surgery and later breast cancer) and 524 females (thyroid surgery only) were compared with regard to pathological thyroid findings, thyroid hormones, thyroid autoimmunity and type of breast cancer. Thyroid autoimmunity, especially antithyroid peroxidase antibodies, significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…They postulated that iodine deficiency might be an important factor in the oncogenic process. Subsequently, other studies recruiting BC patients showed similar results, demonstrating that TPOAb were detected more frequently in BC patients than in the controls [ 88 , 89 , 90 , 91 , 92 ]. Giustarini [ 90 ] detected TPOAb in 36 BC patients, 25 with breast benign disease (BBD) and 100 healthy women.…”
Section: Autoimmune Thyroid Disease and Bcsupporting
confidence: 53%
“…They postulated that iodine deficiency might be an important factor in the oncogenic process. Subsequently, other studies recruiting BC patients showed similar results, demonstrating that TPOAb were detected more frequently in BC patients than in the controls [ 88 , 89 , 90 , 91 , 92 ]. Giustarini [ 90 ] detected TPOAb in 36 BC patients, 25 with breast benign disease (BBD) and 100 healthy women.…”
Section: Autoimmune Thyroid Disease and Bcsupporting
confidence: 53%
“…Interestingly, as our review reported, the phenomenon of increased genetic instability and reduction of tumor immunity in multiple cancer patients was confirmed by the case of the woman with medullary, papillary, and RCC (32), a very rare combination, where even if the patient had no previous endocrine history, her mother was affected by breast cancer, another disease deeply connected to TC (4,(45)(46)(47) and the brother presented with RCC, too. A triple malignant tumor was also reported in a male of the same age with thyroid, kidney, and colon being affected (31), demonstrating common expression paths with integrin avß6 in multiple primary cancer (29).…”
Section: Discussionmentioning
confidence: 70%
“…Studies aimed at defining the association between BC and benign TD, in particular AITD, have produced conflicting results causing a long-lasting debate [153][154][155][156][157][158][159][160][161][162][163][164]. In 2002, Sarlis and colleagues performed a meta-analysis of 13 articles published over the previous 50 years including 14,226 women [153].…”
Section: Autoimmune Thyroid Disease (Aitd) and Breast Cancer (Bc)mentioning
confidence: 99%